Vegetation structure and floristic composition (Case study: Mala Galeh Protected area, Fars Province, Iran) - Moradipour, Leila Leiili; Pourbabaei, Hasan; Hatami, Ahmad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Identifying flora of each region is fundamental for accomplishing other pure and applied researches in biology. Especially, in the ecological conditions of protected area of Male Gale. Data were collected in 96 sampling plots using systematic_ random method. The size of sampling plot was 20 m × 50 m for the tree and shrub species, and 8 m × 8 m for herbaceous species. In this study area, 162 species, 122 genera and 43 families were identified. The largest families were Asteraceae (26 species) and Fabaceae (25 species). The frequency of Asteraceae may be due to grazing in some areas of the region. The life form spectrum includes: Hemichryptophytes (14/01 %), Therophytes (65/4 %), Cryptophytes (76/9 %), Chamaephytes (7.1 %) and Phanerophytes (5.8 %). The abundance of Therophytes and Asteraceae family is refered to destruction of forests in the study area. The highest value of the SIV tree and shrub species layer belong to Quercus brantii species and ZIziphus Mummularia. The highest value of the FIV herbaceous layer belong to Asteraceae family. The Species Important Value (SIV) of vegetation cover indicated that tree, shrubs species and herbaceous species had geometric distribution, broken stick model and lognormal distribution in this area.